2021
DOI: 10.1002/adma.202104867
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond‐Pulsed Perovskite Light‐Emitting Diodes at High Current Density

Abstract: be grown epitaxially on specific substrates, silicon not being one of them.Metal halide perovskite light-emitting diodes (PeLEDs) hold the potential for a new generation of display and lighting technology, [1][2][3][4][5][6][7] featuring high color quality, energy efficiency, and low manufacturing cost. Furthermore, perovskites can be deposited from solutions/inks, which means that they can be deposited on virtually any substrate including silicon. Perovskite LEDs have been shown to be promising for optical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…Shrinking the emission area and driving device in a pulse mode can effectively reduce Joule heating and achieve high injection current at kA cm −2 level without causing excessive deterioration in the device. [152,155,259] Kumawat et al investigated ion migration under pulse-mode operation with the pulse frequencies ranging from 10 Hz to 20 kHz and found the current transient at low frequencies (10-200 Hz) is associated with movement of mobile ions. [260] In contrast, at higher frequencies, the mobile ions cannot respond to the change of the electric field and accordingly the device lifetime increased with the increasing pulse frequency.…”
Section: Thermal Managementmentioning
confidence: 99%
“…Shrinking the emission area and driving device in a pulse mode can effectively reduce Joule heating and achieve high injection current at kA cm −2 level without causing excessive deterioration in the device. [152,155,259] Kumawat et al investigated ion migration under pulse-mode operation with the pulse frequencies ranging from 10 Hz to 20 kHz and found the current transient at low frequencies (10-200 Hz) is associated with movement of mobile ions. [260] In contrast, at higher frequencies, the mobile ions cannot respond to the change of the electric field and accordingly the device lifetime increased with the increasing pulse frequency.…”
Section: Thermal Managementmentioning
confidence: 99%
“…Furthermore, Zhao et al showed a 150 × 200 μm 2 LED obtained from the similar crossover of Ag strip and ITO (Figure 15f). [73] The pulse width was narrower (30 ns) and the duty cycle was reduced by an order of magnitude. After improving the material properties and device configuration, they ultimately achieved an EQE of 1% at 10 kA cm −2 (Figure 15f).…”
Section: Challenges and Advancements Toward Electrically Pumped Lasersmentioning
confidence: 99%
“…[4,258] Therefore, the selection of transport layers with comparable mobility, strong blocking to opposite carriers and small barriers with perovskites is crucial to guarantee balanced charge transport. [73,254] Furthermore, optimization of the energy level alignment by doping in the transport layers or inserting an interfacial layer can also improve the charge balance and further suppress Auger recombination. [259,260] Excitons in perovskites may be dissociated into electrons and holes and migrate to opposite heterogeneous interfaces under electric field, which is detrimental to population inversion.…”
Section: Challenges and Advancements Toward Electrically Pumped Lasersmentioning
confidence: 99%
“…Encouragingly, several important achievements toward this goal have been reported, in particular optically‐pumped continuous‐wave ASE/lasing in perovskite films at both cryogenic and room temperatures (RT), [ 8–10 ] optically‐pumped ASE from a complete perovskite light emitting diode (PeLED) stack, [ 11,12 ] and intense electrical excitation of PeLEDs up to several kA cm −2 current density. [ 13–16 ]…”
Section: Introductionmentioning
confidence: 99%
“…perovskite light emitting diode (PeLED) stack, [11,12] and intense electrical excitation of PeLEDs up to several kA cm −2 current density. [13][14][15][16] Previous studies have shown that Joule heating is a detrimental factor that lowers the device performance at high current injection, even for small-scale PeLEDs excited with sub-microsecond electrical pulses. [13,14,16] Therefore, the reduction of the device operating temperature has been considered as one of the key strategies that likely must be applied in order to achieve electrically pumped perovskite lasing.…”
mentioning
confidence: 99%